Urban Turf Fertilizer Rule for Home Lawn Fertilization - Laurie E. Trenholm (EDIS)
ENH-1089, a 2-page fact sheet by L.E. Trenholm, explains the new state rule regulating urban turf, or home lawn, fertilizer — why it is important, how it affects the homeowner, what the requirements are, exceptions, and existing requirements for commercial lawn care services and golf courses. Published by the UF Department of Environmental Horticulture, January 2008.